Synthesis method of copper-catalyzed allene sulfonyl amidine polymer
The synthesis of polyalkenylsulfonylamidine using a copper catalyst at room temperature addresses the shortcomings in the development of π-bond-coordinated adsorption polymers for metal ions in existing technologies, achieving efficient and environmentally friendly recovery of precious metal ions.
Patent Information
- Application Number
- CN202610356534.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-03-23
- Publication Date
- 2026-05-15
AI Technical Summary
In the existing technology, adsorption-type polymers based on π-bond coordination with metal ions have not been widely developed, making it difficult to achieve mild and efficient adsorption of noble metal ions.
Polyalkenylsulfonylamidine was synthesized via ionic polymerization at room temperature using a copper catalyst. Unsaturated π bonds were formed using 1,3-diyne monomers, disulfonyl azide monomers, and diamine monomers to achieve efficient adsorption.
The synthesized polymer has a high molecular weight and unique allene groups. The reaction conditions are mild, the operation is simple, there are few side reactions, and the yield is high. It meets the requirements of green chemistry and is suitable for the efficient recovery of precious metal ions.
Smart Images

Figure CN122037178A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of novel synthesis technology of copper-catalyzed polymers, and relates to a method for synthesizing copper-catalyzed allene sulfonylamidine polymers. Specifically, it is a method for synthesizing polysulfonylamidine by forming an n-allene intermediate from a disulfonyl azide monomer, a diamine monomer, and a 1,3-diyne monomer at room temperature. Background Technology
[0002] Ion adsorption polymers are a class of functional polymer materials whose structural groups can specifically or non-specifically adsorb ions from solution through mechanisms such as electrostatic interactions, coordination interactions, or ion exchange. Depending on the adsorption mechanism and material properties, these polymers have a wide range of applications, including heavy metal removal, precious metal recovery, and wastewater treatment.
[0003] Compared with traditional metal recycling methods such as pyrometallurgy, hydrometallurgy, and biometallurgy, polymer adsorption methods have lower energy consumption and less environmental pollution, meeting the requirements of green chemistry. Currently, commonly used ion-adsorption polymers mostly adsorb metal ions by forming coordination between heteroatom groups in the polymer backbone and the metal. Sulfur is a large byproduct of the petrochemical industry and has a high affinity for soft transition metal ions with large atomic radii. For example, Yang et al. published "Modification of high-sulfur polymer using a mixture porogen and its application as advanced adsorbents for Au(III) from wastewater" in 2021. This paper describes the preparation of a novel porous high-sulfur polymer (HSP) using a desulfurization method and its application to Au(III) from industrial wastewater. 3+ The polymer exhibits selective recovery by utilizing the coordination of abundant sulfur-containing functional groups in its structure with precious metals to efficiently absorb Au from industrial wastewater. 3+ In addition, thiourea-containing groups and nitrogen-containing polymers are also commonly used in the field of metal ion adsorption under this mechanism.
[0004] Unsaturated bonds provide bonding π orbitals for coordination reactions. Unlike the coordination mechanism between heteroatomic groups and metals mentioned above, the π bonds in unsaturated bonds can combine with transition metals to form coordination, thereby achieving ion adsorption. Adsorption-type polymers based on this mechanism have not yet been widely developed. We aim to develop a novel polymer that achieves efficient adsorption through π-bond coordination with metal ions. Poly(N-sulfonylamidine) is a functional polymer with a unique nitrogen structure, which has been used in fluorescent probes and optoelectronic devices in recent years. We plan to introduce allene and alletene groups into the poly(N-sulfonylamidine) structure to provide unsaturated π bonds for coordination with noble metals. This will allow for the adsorption of noble metals from metal recovery solutions in a mild, efficient, and environmentally friendly manner, providing a simple and green chemistry-compliant solution for ion adsorption. Summary of the Invention
[0005] To develop a method for the efficient preparation of polyalkenylsulfonylamidine under mild conditions, this invention provides a method for the multi-component synthesis of polyalkenylsulfonylamidine from 1,3-diyne monomers, diamine monomers, and disulfonyl azide monomers at room temperature via ionic polymerization. The polymerization steps proposed in this invention are simple, the reaction conditions are mild, the reaction is efficient, and the use of toxic monomers is avoided.
[0006] The technical solution of this invention: A method for synthesizing copper-catalyzed allenylsulfonylamidine polymers includes the following preparation steps: Accurately weigh 1 molar equivalent of disulfonyl azide monomer SA, 1 molar equivalent of disecondary amine monomer Nu, 2 molar equivalents of 1,3-diyne monomer DY, and 3 molar equivalents of organic base DIPEA, dissolve them in a solvent, and add 0.1 molar equivalent of catalyst CuI during the reaction. After stirring at room temperature for 24 h, the reaction is stopped. Then, the reaction solution is precipitated with a precipitant, followed by centrifugation, and the precipitation product is collected three times. The product is dried to constant weight. The general reaction formula is as follows: ; Among them, DY is a 1,3-diyne monomer, SA is a disulfonyl azide monomer, and Nu is a diamine monomer; R and R1 are alkyl groups with fewer than 6 carbon atoms or aromatic groups containing a single benzene ring; R2 is a leaving group -OAc or -OBoc. The structure of the 1,3-diyne monomer DY is as follows: ; The structure of the disulfonyl azide monomer SA is: ; The structure of the binary secondary amine monomer Nu is: ; When the degree of polymerization n is greater than 10, the weight-average molecular weight of the resulting polymer ranges from 8000 to 28000 g / mol, and the polydispersity index ranges from 1.18 to 1.93. The settling agent is diethyl ether; The solvent is dichloromethane, and the organic base is... N , N -Diisopropylethylamine, with cuprous iodide as the copper catalyst.
[0007] The beneficial effects of this invention are: (1) This invention proposes for the first time a one-step synthesis strategy for preparing polyalkenylsulfonylamidine using 1,3-diyne, disulfonyl azide and diamine as monomers under copper catalysis.
[0008] (2) The obtained polymer has unique allene groups and structural chirality. The introduction of allene groups provides unsaturated π bonds to the polymer, and these groups can also be further derivatized as multifunctional building blocks. The polymer has a high molecular weight, with a weight-average molecular weight range of 8000-28000 g / mol.
[0009] (3) The method has mild reaction conditions, simple operation process, few side reactions, high synthesis efficiency, and the yield can usually reach more than 80%, which meets the requirements of green chemistry.
[0010] (4) This type of polymer has good application potential in the field of ion adsorption. It can be used as a high-efficiency adsorbent for the recovery of precious metal ions in wastewater, which helps to realize resource recycling and environmental protection.
[0011] (5) The obtained polymer has excellent chemical stability and can be stored in the air for a long time without significant degradation, making it easy to store and apply in practice. Attached Figure Description
[0012] Figure 1 This is the NMR spectrum of the allene-based polysulfonylamidine compound prepared in Example 1 of this invention.
[0013] Figure 2 This is the NMR spectrum of the allene-based polysulfonylamidine compound prepared in Example 2 of the present invention.
[0014] Figure 3 This is the NMR spectrum of the allene-based polysulfonylamidine compound prepared in Example 3 of the present invention.
[0015] Figure 4 This is the NMR spectrum of the allene-based polysulfonylamidine compound prepared in Example 4 of this invention.
[0016] Figure 5This is the NMR spectrum of the allene-based polysulfonylamidine compound prepared in Example 5 of this invention.
[0017] Figure 6 This is the NMR spectrum of the allene-based polysulfonylamidine compound prepared in Example 6 of the present invention.
[0018] Figure 7 This is the NMR spectrum of the allene-based polysulfonylamidine compound prepared in Example 7 of the present invention.
[0019] Figure 8 This is the NMR spectrum of the allene-based polysulfonylamidine compound prepared in Example 8 of this invention.
[0020] Figure 9 This is the NMR spectrum of the allene-based polysulfonylamidine compound prepared in Example 9 of this invention.
[0021] Figure 10 This is the NMR spectrum of the allene-based polysulfonylamidine compound prepared in Example 10 of the present invention.
[0022] Figure 11 This is the NMR spectrum of the allene-based polysulfonylamidine compound prepared in Example 11 of this invention.
[0023] Figure 12 This is the NMR spectrum of the allene-based polysulfonylamidine compound prepared in Example 12 of this invention.
[0024] Figure 13 This is the NMR spectrum of the allene-based polysulfonylamidine compound prepared in Example 13 of this invention.
[0025] Figure 14 This is the NMR spectrum of the allene-based polysulfonylamidine compound prepared in Example 14 of this invention.
[0026] Figure 15 This is the NMR spectrum of the allene-based polysulfonylamidine compound prepared in Example 15 of this invention.
[0027] Figure 16 This is the NMR spectrum of the allene-based polysulfonylamidine compound prepared in Example 16 of this invention.
[0028] Figure 17 This is the NMR spectrum of the allene-based polysulfonylamidine compound prepared in Example 17 of this invention.
[0029] Figure 18 This is the NMR spectrum of the allene-based polysulfonylamidine compound prepared in Example 18 of this invention. Detailed Implementation
[0030] The specific embodiments of the present invention will be further described below with reference to the accompanying drawings and technical solutions.
[0031] Example 1 In an air atmosphere, the disulfonyl azide monomer SA1 (38 mg, 0.1 mmol), the diamine monomer Nu1 (14.4 mg, 0.1 mmol), and the 1,3-diyne monomer DY1 (31.2 mg, 0.2 mmol) were dissolved in dichloromethane (1 mL). N , N Diisopropylethylamine (41.7 mg, 0.3 mmol) and CuI (1.9 mg, 0.01 mmol) were added during the polymerization reaction. The reaction was stopped after stirring at room temperature for 24 h. The reaction solution was then precipitated with diethyl ether as a settling agent, followed by centrifugation. The precipitate was collected three times and dried to constant weight to obtain powdered product P1 (SA1 / Nu1 / DY1), with the structure shown below. Figure 1 As shown, the yield was 87%. The molecular weight was 11200 g / mol, and the polydispersity index (PDI) was 1.25.
[0032] Take 5 mg of the poly(alkenylsulfonylamidine) product from Example 1 and add it to 10 mL of a 60 mg / L metal ion solution. Stir the mixture at room temperature for 24 h. Centrifuge the suspension and filter it using an aqueous membrane filter. Then, measure the concentration of remaining metal ions in the supernatant using an inductively coupled plasma optical emission spectrometer (ICP-OES). The polymer extraction efficiency formula is: η = ([M n+ ]0- [M n+ ]) / [M n+ ]0× 100%, of which [M n+ ]0 is the initial concentration of metal ions, [M n+ [This refers to the concentration of residual metal ions.] The adsorption test results are shown in Table 1. The experimental data reveals that this allene-based polymer has a high affinity for Fe... 3+ Ag + Au 3+ and Pt 4+ Both showed good adsorption effects.
[0033] Table 1 shows the adsorption efficiency data of the polymer for different metal ions in Example 1 of this invention.
[0034] Example 2 In an air atmosphere, the disulfonyl azide monomer SA1 (38 mg, 0.1 mmol), the diamine monomer Nu2 (21.2 mg, 0.1 mmol), and the 1,3-diyne monomer DY1 (31.2 mg, 0.2 mmol) were dissolved in dichloromethane (1 mL). N , NDiisopropylethylamine (41.7 mg, 0.3 mmol) and CuI (1.9 mg, 0.01 mmol) were added during the polymerization reaction. The reaction was stopped after stirring at room temperature for 24 h. The reaction solution was then precipitated with diethyl ether as a settling agent, followed by centrifugation. The precipitate was collected three times and dried to constant weight to obtain powdered product P2 (SA1 / Nu2 / DY1), with the structure shown below. Figure 2 As shown, the yield was 76%. The molecular weight was 19800 g / mol, and the polydispersity index (PDI) was 1.93.
[0035] Example 3 In an air atmosphere, the disulfonyl azide monomer SA1 (38 mg, 0.1 mmol), the diamine monomer Nu1 (14.4 mg, 0.1 mmol), and the 1,3-diyne monomer DY2 (26.8 mg, 0.2 mmol) were dissolved in dichloromethane (1 mL). N , N Diisopropylethylamine (41.7 mg, 0.3 mmol) and CuI (1.9 mg, 0.01 mmol) were added during the polymerization reaction. The reaction was stopped after stirring at room temperature for 24 h. The reaction solution was then precipitated with diethyl ether as a settling agent, followed by centrifugation. The precipitate was collected three times and dried to constant weight to obtain powdered product P3 (SA1 / Nu1 / DY2), with the structure shown below. Figure 3 As shown, the yield was 86%. The molecular weight was 14600 g / mol, and the polydispersity index (PDI) was 1.18.
[0036] Example 4 In an air atmosphere, the disulfonyl azide monomer SA1 (38 mg, 0.1 mmol), the diamine monomer Nu2 (21.2 mg, 0.1 mmol), and the 1,3-diyne monomer DY2 (26.8 mg, 0.2 mmol) were dissolved in dichloromethane (1 mL). N , N Diisopropylethylamine (41.7 mg, 0.3 mmol) and CuI (1.9 mg, 0.01 mmol) were added during the polymerization reaction. The reaction was stopped after stirring at room temperature for 24 h. The reaction solution was then precipitated with diethyl ether as a settling agent, followed by centrifugation. The precipitate was collected three times and dried to constant weight to obtain a powdered product P4 (SA1 / Nu2 / DY2), with the structure shown below. Figure 4 As shown, the yield was 76%. The molecular weight was 23,000 g / mol, and the polydispersity index (PDI) was 1.56.
[0037] Example 5 In an air atmosphere, the disulfonyl azide monomer SA1 (38 mg, 0.1 mmol), the diamine monomer Nu1 (14.4 mg, 0.1 mmol), and the 1,3-diyne monomer DY3 (21.6 mg, 0.2 mmol) were dissolved in dichloromethane (1 mL). N , N Diisopropylethylamine (41.7 mg, 0.3 mmol) and CuI (1.9 mg, 0.01 mmol) were added during the polymerization reaction. The reaction was stopped after stirring at room temperature for 24 h. The reaction solution was then precipitated with diethyl ether as a settling agent, followed by centrifugation. The precipitate was collected three times and dried to constant weight to obtain powdered product P5 (SA1 / Nu1 / DY3), with the structure shown below. Figure 5 As shown, the yield was 82%. The molecular weight was 14000 g / mol, and the polydispersity index (PDI) was 1.24.
[0038] Example 6 In an air atmosphere, the disulfonyl azide monomer SA1 (38 mg, 0.1 mmol), the diamine monomer Nu1 (14.4 mg, 0.1 mmol), and the 1,3-diyne monomer DY4 (30.8 mg, 0.2 mmol) were dissolved in dichloromethane (1 mL). N , N Diisopropylethylamine (41.7 mg, 0.3 mmol) and CuI (1.9 mg, 0.01 mmol) were added during the polymerization reaction. The reaction was stopped after stirring at room temperature for 24 h. The reaction solution was then precipitated with diethyl ether as a settling agent, followed by centrifugation. The precipitate was collected three times and dried to constant weight to obtain powdered product P6 (SA1 / Nu1 / DY4), with the structure shown below. Figure 6 As shown, the yield was 88%. The molecular weight was 14600 g / mol, and the polydispersity index (PDI) was 1.37.
[0039] Example 7 In an air atmosphere, the disulfonyl azide monomer SA1 (38 mg, 0.1 mmol), the diamine monomer Nu2 (21.2 mg, 0.1 mmol), and the 1,3-diyne monomer DY4 (30.8 mg, 0.2 mmol) were dissolved in dichloromethane (1 mL). N , NDiisopropylethylamine (41.7 mg, 0.3 mmol) and CuI (1.9 mg, 0.01 mmol) were added during the polymerization reaction. The reaction was stopped after stirring at room temperature for 24 h. The reaction solution was then precipitated with diethyl ether as a settling agent, followed by centrifugation. The precipitate was collected three times and dried to constant weight to obtain powdered product P7 (SA1 / Nu2 / DY4), with the structure shown below. Figure 7 As shown, the yield was 76%. The molecular weight was 15500 g / mol, and the polydispersity index (PDI) was 1.72.
[0040] Example 8 In an air atmosphere, the disulfonyl azide monomer SA1 (38 mg, 0.1 mmol), the diamine monomer Nu1 (14.4 mg, 0.1 mmol), and the 1,3-diyne monomer DY5 (26.4 mg, 0.2 mmol) were dissolved in dichloromethane (1 mL). N , N Diisopropylethylamine (41.7 mg, 0.3 mmol) and CuI (1.9 mg, 0.01 mmol) were added during the polymerization reaction. The reaction was stopped after stirring at room temperature for 24 h. The reaction solution was then precipitated with diethyl ether as a settling agent, followed by centrifugation. The precipitate was collected three times and dried to constant weight to obtain powdered product P8 (SA1 / Nu1 / DY5), with the structure shown below. Figure 8 As shown, the yield was 77%. The molecular weight was 9100 g / mol, and the polydispersity index (PDI) was 1.18.
[0041] Example 9 In an air atmosphere, the disulfonyl azide monomer SA1 (38 mg, 0.1 mmol), the diamine monomer Nu2 (21.2 mg, 0.1 mmol), and the 1,3-diyne monomer DY5 (26.4 mg, 0.2 mmol) were dissolved in dichloromethane (1 mL). N , N Diisopropylethylamine (41.7 mg, 0.3 mmol) and CuI (1.9 mg, 0.01 mmol) were added during the polymerization reaction. The reaction was stopped after stirring at room temperature for 24 h. The reaction solution was then precipitated with diethyl ether as a settling agent, followed by centrifugation. The precipitate was collected three times and dried to constant weight to obtain a powdered product P9 (SA1 / Nu2 / DY5), with the structure shown below. Figure 9 As shown, the yield was 76%. The molecular weight was 19000 g / mol, and the polydispersity index (PDI) was 1.46.
[0042] Example 10 In an air atmosphere, the disulfonyl azide monomer SA1 (38 mg, 0.1 mmol), the diamine monomer Nu1 (14.4 mg, 0.1 mmol), and the 1,3-diyne monomer DY6 (25.2 mg, 0.2 mmol) were dissolved in dichloromethane (1 mL). N , N Diisopropylethylamine (41.7 mg, 0.3 mmol) and CuI (1.9 mg, 0.01 mmol) were added during the polymerization reaction. The reaction was stopped after stirring at room temperature for 24 h. The reaction solution was then precipitated with diethyl ether as a settling agent, followed by centrifugation. The precipitate was collected three times and dried to constant weight to obtain a powdered product P10 (SA1 / Nu1 / DY6), with the structure shown below. Figure 10 As shown, the yield was 86%. The molecular weight was 9700 g / mol, and the polydispersity index (PDI) was 1.09.
[0043] Example 11 In an air atmosphere, the disulfonyl azide monomer SA1 (38 mg, 0.1 mmol), the diamine monomer Nu2 (21.2 mg, 0.1 mmol), and the 1,3-diyne monomer DY6 (25.2 mg, 0.2 mmol) were dissolved in dichloromethane (1 mL). N , N Diisopropylethylamine (41.7 mg, 0.3 mmol) and CuI (1.9 mg, 0.01 mmol) were added during the polymerization reaction. The reaction was stopped after stirring at room temperature for 24 h. The reaction solution was then precipitated with diethyl ether as a settling agent, followed by centrifugation. The precipitate was collected three times and dried to constant weight to obtain a powdered product P11 (SA1 / Nu2 / DY6), with the structure shown below. Figure 11 As shown, the yield was 78%. The molecular weight was 12100 g / mol, and the polydispersity index (PDI) was 1.18.
[0044] Example 12 In an air atmosphere, the disulfonyl azide monomer SA1 (38 mg, 0.1 mmol), the diamine monomer Nu1 (14.4 mg, 0.1 mmol), and the 1,3-diyne monomer DY7 (35.2 mg, 0.2 mmol) were dissolved in dichloromethane (1 mL). N , NDiisopropylethylamine (41.7 mg, 0.3 mmol) and CuI (1.9 mg, 0.01 mmol) were added during the polymerization reaction. The reaction was stopped after stirring at room temperature for 24 h. The reaction solution was then precipitated with diethyl ether as a settling agent, followed by centrifugation. The precipitate was collected three times and dried to constant weight to obtain a powdered product P12 (SA1 / Nu1 / DY7), with the structure shown below. Figure 12 As shown, the yield was 88%. The molecular weight was 22800 g / mol, and the polydispersity index (PDI) was 1.26.
[0045] Example 13 In an air atmosphere, the disulfonyl azide monomer SA1 (38 mg, 0.1 mmol), the diamine monomer Nu2 (21.2 mg, 0.1 mmol), and the 1,3-diyne monomer DY7 (35.2 mg, 0.2 mmol) were dissolved in dichloromethane (1 mL). N , N Diisopropylethylamine (41.7 mg, 0.3 mmol) and CuI (1.9 mg, 0.01 mmol) were added during the polymerization reaction. The reaction was stopped after stirring at room temperature for 24 h. The reaction solution was then precipitated with diethyl ether as a settling agent, followed by centrifugation. The precipitate was collected three times and dried to constant weight to obtain a powdered product P13 (SA1 / Nu2 / DY7), with the structure shown below. Figure 13 As shown, the yield was 85%. The molecular weight was 28,000 g / mol, and the polydispersity index (PDI) was 1.34.
[0046] Example 14 In an air atmosphere, the disulfonyl azide monomer SA1 (38 mg, 0.1 mmol), the diamine monomer Nu1 (14.4 mg, 0.1 mmol), and the 1,3-diyne monomer DY8 (39.6 mg, 0.2 mmol) were dissolved in dichloromethane (1 mL). N , N Diisopropylethylamine (41.7 mg, 0.3 mmol) and CuI (1.9 mg, 0.01 mmol) were added during the polymerization reaction. The reaction was stopped after stirring at room temperature for 24 h. The reaction solution was then precipitated with diethyl ether as a settling agent, followed by centrifugation. The precipitate was collected three times and dried to constant weight to obtain powdered product P14 (SA1 / Nu1 / DY8), with the structure shown below. Figure 14 As shown, the yield was 78%. The molecular weight was 8100 g / mol, and the polydispersity index (PDI) was 1.22.
[0047] Take 5 mg of the poly(alkenylsulfonylamidine) product from Example 14 and add it to 10 mL of a 60 mg / L metal ion solution. Stir the mixture at room temperature for 24 h. Centrifuge the suspension and filter it using an aqueous membrane filter. Then, measure the concentration of remaining metal ions in the supernatant using an inductively coupled plasma optical emission spectrometer (ICP-OES). The polymer extraction efficiency formula is: η = ([M n+ ]0- [M n+ ]) / [M n+ ]0× 100%, of which [M n+ ]0 is the initial concentration of metal ions, [M n+ [This refers to the concentration of residual metal ions.] The adsorption test results are shown in Table 2. The experimental data reveals that this triterene-based polymer has a high affinity for Fe... 3+ Ag + Au 3+ and Pt 4+ Both showed good adsorption effects.
[0048] Table 2 shows the adsorption efficiency data of the polymer for different metal ions in Example 14 of this invention.
[0049] Example 15 In an air atmosphere, the disulfonyl azide monomer SA1 (38 mg, 0.1 mmol), the diamine monomer Nu2 (21.2 mg, 0.1 mmol), and the 1,3-diyne monomer DY9 (46.8 mg, 0.2 mmol) were dissolved in dichloromethane (1 mL). N , N Diisopropylethylamine (41.7 mg, 0.3 mmol) and CuI (1.9 mg, 0.01 mmol) were added during the polymerization reaction. The reaction was stopped after stirring at room temperature for 24 h. The reaction solution was then precipitated with diethyl ether as a settling agent, followed by centrifugation. The precipitate was collected three times and dried to constant weight to obtain a powdered product P15 (SA1 / Nu2 / DY9), with the structure shown below. Figure 15 As shown, the yield was 86%. The molecular weight was 20,000 g / mol, and the polydispersity index (PDI) was 1.72.
[0050] Example 16 In an air atmosphere, the disulfonyl azide monomer SA2 (28.8 mg, 0.1 mmol), the diamine monomer Nu2 (21.2 mg, 0.1 mmol), and the 1,3-diyne monomer DY9 (46.8 mg, 0.2 mmol) were dissolved in dichloromethane (1 mL). N , NDiisopropylethylamine (41.7 mg, 0.3 mmol) and CuI (1.9 mg, 0.01 mmol) were added during the polymerization reaction. The reaction was stopped after stirring at room temperature for 24 h. The reaction solution was then precipitated with diethyl ether as a settling agent, followed by centrifugation. The precipitate was collected three times and dried to constant weight to obtain a powdered product P16 (SA2 / Nu2 / DY9), with the structure shown below. Figure 16 As shown, the yield was 80%. The molecular weight was 14600 g / mol, and the polydispersity index (PDI) was 1.58.
[0051] Example 17 In an air atmosphere, the disulfonyl azide monomer SA2 (38 mg, 0.1 mmol), the diamine monomer Nu1 (14.4 mg, 0.1 mmol), and the 1,3-diyne monomer DY10 (51.2 mg, 0.2 mmol) were dissolved in dichloromethane (1 mL). N , N Diisopropylethylamine (41.7 mg, 0.3 mmol) and CuI (1.9 mg, 0.01 mmol) were added during the polymerization reaction, and the reaction was stopped after stirring at room temperature for 24 h. The reaction solution was then precipitated with diethyl ether as a settling agent, followed by centrifugation, which was repeated three times to collect the precipitate. The product was dried to constant weight to obtain a powdered product P17 (SA2 / Nu1 / DY10), with the structure shown below. Figure 17 As shown, the yield was 81%. The molecular weight was 8800 g / mol, and the polydispersity index (PDI) was 1.20.
[0052] Example 18 In an air atmosphere, the disulfonyl azide monomer SA2 (28.8 mg, 0.1 mmol), the diamine monomer Nu2 (21.2 mg, 0.1 mmol), and the 1,3-diyne monomer DY10 (51.2 mg, 0.2 mmol) were dissolved in dichloromethane (1 mL). N , N Diisopropylethylamine (41.7 mg, 0.3 mmol) and CuI (1.9 mg, 0.01 mmol) were added during the polymerization reaction. The reaction was stopped after stirring at room temperature for 24 h. The reaction solution was then precipitated with diethyl ether as a settling agent, followed by centrifugation. The precipitate was collected three times and dried to constant weight to obtain a powdered product P18 (SA2 / Nu2 / DY10), with the structure shown below. Figure 18 As shown, the yield was 78%. The molecular weight was 11600 g / mol, and the polydispersity index (PDI) was 1.43.
Claims
1. A method for synthesizing copper-catalyzed allenylsulfonylamidine polymers, characterized in that, Includes the following steps: Accurately weigh 1 molar equivalent of disulfonyl azide monomer SA, 1 molar equivalent of disecondary amine monomer Nu, 2 molar equivalents of 1,3-diyne monomer DY, and 3 molar equivalents of organic base DIPEA, dissolve them in a solvent, and add 0.1 molar equivalent of catalyst CuI during the reaction. After stirring at room temperature for 24 h, the reaction is stopped. Then, the reaction solution is precipitated with a precipitant, followed by centrifugation, and the precipitation product is collected three times. The product is dried to constant weight. The general reaction formula is as follows: ; Among them, DY is a 1,3-diyne monomer, SA is a disulfonyl azide monomer, and Nu is a diamine monomer; R and R1 are alkyl groups with fewer than 6 carbon atoms or aromatic groups containing a single benzene ring; R2 is a leaving group -OAc or -Oboc. When the degree of polymerization n is greater than 10, the weight-average molecular weight of the resulting polymer ranges from 8000 to 28000 g / mol, and the polydispersity index ranges from 1.18 to 1.
93.
2. The method for synthesizing copper-catalyzed allenylsulfonylamidine polymers according to claim 1, characterized in that, The structure of the 1,3-diyne monomer DY is as follows: ; The structure of the disulfonyl azide monomer SA is: ; The structure of the binary secondary amine monomer Nu is: 。 3. The method for synthesizing copper-catalyzed allenylsulfonylamidine polymers according to claim 1, characterized in that, The settling agent is diethyl ether.
4. The method for synthesizing copper-catalyzed allenylsulfonylamidine polymers according to claim 1, characterized in that, The solvent is dichloromethane, and the organic base is... N , N -Diisopropylethylamine, with cuprous iodide as the copper catalyst.